Developing a Heuristic Algorithm to Solve Uncertainty Problem of Resource Allocation in a Software Project Scheduling - Al-Jawaherry, Marwa Adeeb; Abdulmajeed, Ashraf Abdulmunim; Tawfeeq, Tawfeeq Mokdad (Iraqi Journal of Science, 2022)
In project management process, the objective is to define and develop a model for planning, scheduling, controlling, and monitoring different activities of a particular project. Time scheduling plays an important role in successful implementation of various activities and general outcome of project. In practice, various factors cause projects to suffer from time delay in accomplishing the activities. One important reason is imprecise knowledge about time duration of activities. This study addresses the problem of project scheduling in uncertain resource environments, which are defined by uncertain activity durations. The study presents a solution of the levelling and allocation problems for projects that have some uncertain activities. The resources are minimised using resource levelling based on a proposed heuristic algorithm with limited duration. The algorithm performs the resource scheduling (levelling and allocation) for minimum moments. The efficiency of the proposed algorithm is indicated by the resource improvement coefficient and rate of resource utilisation.